Bauhaus Graduates’ Urban Planning in the 1950s - Tomita, Hideo (International Planning History Society Proceedings, 2024)
Graduates from the Bauhaus implemented urban planning in Europe, the Middle East, and Asia during the 1950s. We clarified their urban planning activities by analysing their designs using published reports and books. Our study reveals the following four points. First, the German Building Academy led urban planning in East Germany, and urban planners, including Edmund Collein (1906–92) and Selman Selmanagic (1905–86), held important positions, and designed new cities in East Germany. Second, in Hungary, Tibor Weiner (1906–65) designed the Sztálinváros. Weiner was involved in constructing the new socialist city of Orsk in the USSR in the 1930s. Third, Arieh Sharon (1900–84) designed 15 new cities in Israel. Fourth, graduate Konrad Püschel (1907–97) was involved in the post-war reconstruction of the North Korean city of Hamhung. All held government or academic positions and led new urban planning in East Germany, Hungary, and Israel. Bauhaus graduates commonly conducted thorough research on the nature, history, culture, and settlement of the area before urban planning using the results of their urban planning. These characteristics were influenced by the general urban planning methods of the 1950s and the analytically oriented education in Bauhaus.